The Effectiveness Of Using Jigsaw Technique To Improve Reading Comprehension Of First Graders Of Smk 4 Kendari In 2015/ 2016 Academic Years - Surahmawati, Dahlia; Hanafi, Hilaluddin; Badara, Aris (Halu Oleo University, 2016)
This study aimed to find whether teaching narrative text by using Jigsaw technique effective for studentsâ€™ reading comprehension of first graders at SMK 4 Kendari and to describe the students perception about Jigsaw technique. The researcher limited this study on literal and interpretative comprehension. This study was pre experimental design. The population of this study was 97 students (taken from 3 classes of TKJ). Through SPSS 21.0, the researcher gotten the students of TKJ A is the sample of this study. The numbers of sample were 32 students. The instrument of this study was reading test and perception questionnaire. The result of this study showed that Jigsaw technique gave a significant effect on the students reading comprehension at first graders of SMK4 Kendari. It can be seen from the result of SPSS 21.0 (T-Test), it showed the probability value Asymp (Sig. 2 Tailed) was 0.000 < 0.05 ( p â‰¤ 0.05) and t count was 11.33 > t table (2.039). It means that the second hypothesis (H1) was accepted.